SKRINING FITOKIMIA DAN UJI ANTIOKSIDAN TERHADAP EKSTRAK BUNGA Limnocharis flava L DENGAN METODE DPPH - Ermi Abriyani; Lia Fikayuniar; Mia Anisa Silvi; Arie Wichandar (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Genjer (Limnocharis flava L.) is of plants that bloom throughout the year. The part that can be used of Limnocharis flava L. is leaves, but more people used stems and flowers of Limnocharis flava L. for consumption. The present study has aim to determine the phytochemical screening and antioxidants activity assay of Limnocharis flava L. bloom extracts. Method of the research are extraction by maceration, screening phytochemical, DPPH method which is by measuring the capture of synthetic radicals in polar organic solvents at room temperature. The results of phytochemical screening of Limnocharis flava L. bloom are flavonoid, saponin, tannin, polyphenols, quinone. Antioxidant activity assay of Limnocharis flava L. bloom from three extracts have resulted IC50 value from methanol extract 61.4224 ppm, ethyl acetate extract 160.4368 ppm and n-hexane 433,2932 ppm. Methanol extract has a stronger antioxidant compared to ethyl acetate and n-hexane extracts by DPPH method.